2015
DOI: 10.5539/ijbm.v10n6p287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bank Specific and Macroeconomic Determinants of Banking Profitability: A Study on Bangladesh

Abstract: The study designed to investigate bank specific and macroeconomic determinants of profitability considering 299 observations of 35 banks in Bangladesh during 2003 to 2013. The investigation process considers all types of local Bangladeshi banks, OLS fixed effect and two step system GMM model. The results report that credit risk, cost efficiency, GDP growth and real interest rate effects profitability negatively; and capital adequacy, liquidity, size, inflation and stock market turnover effect profitability pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
73
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 29 publications
(69 reference statements)
19
73
0
5
Order By: Relevance
“…They used the GMM approach and results showed that the capital adequacy ratio has a positive influence on bank profitability for BRICS countries. Chowdhury (2015); Noman et al (2015) and Ozili (2016) also reached a similar conclusion by using the same method in their studies. Moreover, by using regression analysis, Molyneux and Thornton (1992); Abreu and Mendes (2001); Dawood (2014); Pradhan and Shrestha (2016) and Khatun and Siddiqui (2016) identified capital adequacy as the most important factor which influences bank profitability.…”
Section: Buchory (2015) Indonesia Regressionsupporting
confidence: 59%
See 1 more Smart Citation
“…They used the GMM approach and results showed that the capital adequacy ratio has a positive influence on bank profitability for BRICS countries. Chowdhury (2015); Noman et al (2015) and Ozili (2016) also reached a similar conclusion by using the same method in their studies. Moreover, by using regression analysis, Molyneux and Thornton (1992); Abreu and Mendes (2001); Dawood (2014); Pradhan and Shrestha (2016) and Khatun and Siddiqui (2016) identified capital adequacy as the most important factor which influences bank profitability.…”
Section: Buchory (2015) Indonesia Regressionsupporting
confidence: 59%
“…Noman et al (2015) Bangladesh GMM Defined that real interest rate affects the probability of the banks negatively whereas capital adequacy, size and inflation rate have a positive influence. In addition to these, some studies indicated the relationship between economic growth and bank profitability.…”
Section: Buchory (2015) Indonesia Regressionmentioning
confidence: 99%
“…This finding implies that banks with higher CAR are more profitable. The positive relationship between CAR and ROA is consistent with the results of Noman et al (2015). The estimated coefficient of the BURD is statistically significant and negative, which implies that increases in banks' non-interest expense decrease banks' financial performance.…”
Section: Resultssupporting
confidence: 78%
“…The positive relationship between the inflation rate and banks' performance suggests that in periods of high inflation, banks control interest rate changes which may lead to profit generation and, thus, in turn, affects banks' profitability positively. The positive impact of inflation on the performance of banks has also been reported by some previous studies like Noman et al (2015) and Wasiuzzaman and Tarmizi (2010). On the other hand, Kanwal and Nadeem (2013) found the negative effect of the rate of inflation on banks' performance.…”
Section: Results Of Banks' Performance Modelsupporting
confidence: 49%
See 1 more Smart Citation